2018
DOI: 10.26822/iejee.2018438134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Morning Physical Activity on Elementary School Students Physical Fitness and Sociality

Abstract: As part of the Comprehensive School Physical Activity Program, we investigated how early morning physical activity affects elementary school students' physical fitness and sociality. Seventy-five boys in 6th grade of one elementary school located in G Metropolitan City, Korea comprised the experimental group that participated in early morning physical activity for 6 months. The control group did not perform said activities. Experimental design for this study adopted pre-and post-measurement and comparison meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The opinion of Physical activity in childhood is closely associated with health. Physical activity refers to all movements of the body caused by the contraction of the skeletal muscles [32] and plays a vital role in energy consumption [33]. Therefore, physical activity or sports should always be given to early childhood.…”
Section: Resultsmentioning
confidence: 99%
“…The opinion of Physical activity in childhood is closely associated with health. Physical activity refers to all movements of the body caused by the contraction of the skeletal muscles [32] and plays a vital role in energy consumption [33]. Therefore, physical activity or sports should always be given to early childhood.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies on "0th-period PE class" have been conducted in Korea, and Jeon et al [15] found that the participation of middle school students had a statistically significant effect on perceived enjoyment and learning attitudes. Furthermore, an intervention study at the elementary school also concluded that the early morning exercise program significantly improves social skills, autonomy, and stability [16]. Finally, for the high school case, a 3-year long-term morning exercise program positively influenced participants' fitness test scores, physical self-concept, and academic achievement [17].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the exact definition was “0th period physical education class” [ 15 ]. In foreign research, the terms “early morning physical exercises” and “early morning physical activity” were used [ 16 , 17 ]. This class is organized in schools in South Korea, as determined by the principal or physical education teacher [ 12 ].…”
Section: Introductionmentioning
confidence: 99%